ENHANCING BUSINESS SKILLS OF MICRO WAQF BANK CLIENTS THROUGH PESANTREN COMMUNITY VOCATIONAL TRAINING CENTRES IN INDONESIA - FAUZI, MUHAMAD; Kamil, Adinda Zahra Raisya; Masykur, Harun (Diponegoro Journal of Islamic Economics and Business, 2025)
The Micro Waqf Bank (BWM) focuses on financing and business mentoring, and the Community Vocational Training Centre (BLKK) emphasises the development of technical skills, both based in Islamic boarding schools (pesantren), share a core value of economic empowerment, but have yet to demonstrate a synergistic pattern in implementing integrated empowerment. The research aims to identify patterns for enhancing the business skills of Micro Waqf Bank clients through the pesantren-based Community Vocational Training Centre. The qualitative research method uses a Systematic Literature Review (SLR) approach. Data were collected from international journals indexed by Scopus, ERA, MyCite, WoS, DOAJ, Google Scholar, and SINTA, published between 2019 and 2025. Data analysis was conducted using content analysis with Evidence-Based Software Engineering (EBSE) techniques. The results identified seven main patterns in improving the business skills of Micro Waqf Bank clients through the pesantren community vocational training centre: initial needs and business potential identification, business training planning, training implementation, business mentoring, access to financing and capital, and strengthening networks and marketing. The research implications highlight the importance of pesantren-based economic empowerment synergy that integrates financing and skills training comprehensively to enhance clients' business independence. The research limitation lies in using a literature review method without empirical field data, making it conceptual and requiring further verification. The research contributes to developing a systematic pattern for business skills improvement as a model for integrated empowerment programmes based in pesantren. Future research should conduct empirical field studies to test this pattern's effectiveness and explore supporting and inhibiting factors.